Optimizing reaction condition of octenyl succinic anhydride on heat-moisture-treated sago starch and its application for biodegradable film - DEWI, Angela Myrra Puspita; SANTOSO, Umar; PRANOTO, Yudi; MARSENO, Djagal Wiseso (Food Science and Technology, 2023)
This study presented the impact of pH and octenyl succinic anhydride (OSA) concentration on the esterification reaction of heat-moisture-treated sago starch (HMT-S) using response surface methodology to achieve optimum degree of substitution (DS), reaction efficiency (RE), and water contact angle (CA). The results showed that HMT-OSA sago starch (HMT-OS) starch exhibited an optimum pH of 7.26 and an OSA concentration of 4.53%. The DS value, RE, and water CA of optimized HMT-OS starch were 0.0121, 33.07%, and 90.11°, respectively. Furthermore, the optimized HMT-OS was used to evaluate the effect of starch modification on film characteristics. HMT-OS film has the best moisture-proof and mechanical properties compared to control (NS), HMT-S, and N-OS films, as indicated by lower water vapor permeability (28.69 g H2O.mm/s.m2.Pa × 10-11), water solubility (26.61%), higher CA (104.40°), elongation at break (85.63%), and transparency (3.25% mm-1). According to the scanning electron micrographic images, the absence of cracks or pores was attributed to the waterproof properties and flexibility of the film. Conversely, x-ray diffraction results showed that the crystallinity of HMT-OS film decreased to 36.05%.